Cutibacterium acnes regulates the epidermal barrier properties of HPV-KER human immortalized keratinocyte cultures - Beáta Szilvia Bolla (Nature Portfolio, 2020)
Abstract Our skin provides a physical barrier to separate the internal part of our body from the environment. Maintenance of complex barrier functions is achieved through anatomical structures in the skin, the stratified squamous epithelium specialized junctional organelles, called tight junctions (TJs). Several members of our microbial communities are known to affect the differentiation state and function of the colonized organ. Whether and how interactions between skin cells and cutaneous microbes, including Cutibacterium acnes (C. acnes), modify the structure and/or function of our skin is currently only partly understood. Thus, in our studies, we investigated whether C. acnes may affect the epidermal barrier using in vitro model systems. Real-time cellular analysis showed that depending on the keratinocyte differentiation state, the applied C. acnes strains and their dose, the measured impedance values change, together with the expression of selected TJ proteins. These may reflect barrier alterations, which can be partially restored upon antibiotic–antimycotic treatment. Our findings suggest that C. acnes can actively modify the barrier properties of cultured keratinocytes, possibly through alteration of tight cell-to-cell contacts. Similar events may play important roles in our skin, in the maintenance of cutaneous homeostasis.